Curt Lange: implicações sociorraciais do termo "mulatismo musical" - Hudson Ditherman Francisco Rosa (2021)
The aim of this research is to investigate the socio-racial implications of the term “mulatismo musical” coined by musicologist Francisco Curt Lange. From the selection and analysis of items of Lange’s publications I broach four important notions pervading his thought: culture, musicology, race and colonialism. Assuming an anticolonial perspective, the theoretical framework includes an array of fields of knowledge, such as Musicology, History, Sociology, Philosophy, and contemporary works on coloniality, race and racism. The study led to a greater understanding of the musicologist’s ideas on “mulatismo musical”. It also showed that the emphasis Curt Lange gave to the term along more than half a century of dissemination of his work contributed to strengthen the discourse on miscegenation in Brazil, especially within the music studies.